Organizational boundaries of medical practice: The case of physician ownership of ancillary services - John E. Schneider; Robert L. Ohsfeldt; Cara M. Scheibling; Sarah A. Jeffers (Health Economics Review, 2012)
Physician ownership of in-office ancillary services (IOASs) has come under increasing scrutiny. Advocates of argue that IOASs allow physicians to supervise the quality and coordination of care. Critics have argued that IOASs create financial incentives for physicians to increase ancillary service volume. In this paper we develop a conceptual framework to evaluate the tradeoffs associated with physician ownership of IOASs. There is some evidence supporting the existence of scope and transaction economies in IOASs. Improvement in flow and continuity of care are likely to generate scope economies and improvements in quality monitoring and reductions in consumer transaction costs are likely to generate transaction economies. Other factors include the capture of upstream and downstream profits, but these incentives are likely to be small compared to scope and transaction economies. Policy debates on the merits of IOASs should include an explicit assessment of these tradeoffs. This research was supported in part by funding from the American Association of Orthopaedic Surgeons (AAOS).
Keywords: 330